Homogeneous, nonlinear, load-flow algorithm for HV-AC and compound HV-ACDC systems - Zaborszky, J.; Ilić-Spong, M.; Whang, K.W. (International journal of electrical power & energy systems, 1982)
A general load-flow algorithm of the Jacobi or Gauss-Seidel type is introduced, which is constructed quite differently from the many algorithms described in the extensive literature on this subject. The algorithm is well suited for parallel processing at whatever level of parellelism. Nonlinear relationships for injections such as composite loads, nonlinear transmission ‘lines’ such as TCUL and phase-shifting transformers, AC/DC converters and multiterminal DC components are handled homogeneously by the basic algorithm without modifications. Constraints on voltage, current and power can be included without involving the complexities of nonlinear programming. A homogeneous model for multiterminal HV-DC networks is introduced which allows such networks to be treated as quite regular AC components.